2020
DOI: 10.3390/a13050121
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Deep Learning Models for Forecasting Cryptocurrency Time-Series

Abstract: Nowadays, cryptocurrency has infiltrated almost all financial transactions; thus, it is generally recognized as an alternative method for paying and exchanging currency. Cryptocurrency trade constitutes a constantly increasing financial market and a promising type of profitable investment; however, it is characterized by high volatility and strong fluctuations of prices over time. Therefore, the development of an intelligent forecasting model is considered essential for portfolio optimization and decision maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 40 publications
0
39
0
1
Order By: Relevance
“…A common method for combining base models is averaging. Averaging has the advantage of reducing variance in the predictions based on the understanding that the based models will not make similar errors in their predictions [ 57 ]. It involves the generation and training of a specific number of models separately and combining them through the computation of the mean of the predicted class scores.…”
Section: Resultsmentioning
confidence: 99%
“…A common method for combining base models is averaging. Averaging has the advantage of reducing variance in the predictions based on the understanding that the based models will not make similar errors in their predictions [ 57 ]. It involves the generation and training of a specific number of models separately and combining them through the computation of the mean of the predicted class scores.…”
Section: Resultsmentioning
confidence: 99%
“…However, they do not evaluate whether the model properly fits the data while the residuals are usually dedicated to evaluating this. Therefore, we evaluated the forecasting reliability of the proposed models by examining for auto-correlation in the errors [35,36]. Figures 3-5 illustrate the autocorrelation function (ACF) diagram for Dez reservoir inflow forecasting by FSF-ARIMA model, RANN model, and Hybrid model, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Although the hybrid model outperformed the RANN and FSF-ARIMA models, the ACF plots revealed that all models were unable to make reliable forecasts. It is worth mentioning that employing a more advanced model such as long short-term memory (LSTM) and deep learning techniques like the Convolutional Neural Network (CNN), as well as their combination, CNN-LSTM [35,36], can improve the accuracy of forecasting. In addition, these new models have shown more reliable forecasts [35,36].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Let us quote other relevant works. Shintate & Pichl (2019) , Ji, Kim & Im (2019) , Livieris et al (2020) , Lamothe-Fernández et al (2020) , and Chen, Li & Sun (2020) predicted Bitcoin price at different frequencies using several machine learning techniques and investigating the importance of the sample dimension. Greaves & Au (2015) investigated the predictive power of blockchain network-based features on the bitcoin price.…”
Section: Related Workmentioning
confidence: 99%